Prinsip Tolong-Menolong Dalam Islam (Ekplorasi Dalam Ayat Alqur’an, Sirah Nabiyah Dan Piagam Madinah) - albahri, Albahri; Pasiska, Pasiska; Kurniati, Anita (El-Ghiroh : Jurnal Studi Keislaman, 2023)
This concept underlines the help of help in Islam through the tracing contained in the verses of the Qur'an, the Prophet's Sirah and the Medina Charter Please help others is an unavoidable sunnatullah.Every human being is free to choose the desired livelihood and will have a share in his efforts. A person will not earn more than what he has done. Qualitative research method with a literature study research approach with data sources obtained through documents, literture, both in the form of articles, books and others relevant to research. The results concluded that each individual's physical and mental well-being is different, as is their ability to earn a living. Man was created by God on earth to fill and prosper life and this life in accordance with the order and law of God's law. Humans are qudrati as individual beings and social beings, that is, humans need each other, both in exchanging ideas, interacting, and completing needs in everyday life. In carrying out life and life, Islam in addition to proclaiming the right creed and worship as a means of liaison between servants and their creators also formulates good and correct procedures in muamalah as a liaison between humans and each other. Muamalah are God's must-obey rules that govern man's relationship with man in relation to acquiring and developing property, as well as defending the rights of society.